INVESTIGATING METRICAL CONTEXT EFFECTS ON ANTICIPATORY COARTICULATION IN CONNECTED SPEECH DEVELOPMENT - Adkins, Jillian (Proc Int Congr Phon Sci, 2019)
If rhythm acquisition is influenced by the development of articulatory timing, then metrical structure might be expected to condition this timing. This study tested this hypothesis by investigating anticipatory effects of an upcoming noun on the production of a preceding determiner, under the assumption that anticipatory coarticulation indexes chunking. Simple S-V-O sentences were elicited from 5-year-olds, 8-year-olds, and adults. The V was either monosyllabic packed or disyllabic patted. The O was a determiner phrase where nouns varied either in onset place-of-articulation (POA; tack vs. cat) or in their rhymes (tack vs. toot). Acoustic analyses of determiner schwa F1 and F2 showed no effect of verb on schwa coarticulation. Given other results, including an interaction between age group and POA, the findings suggest that the acquisition of articulatory timing is independent of metrical structure, even if this timing is related to speech rhythm acquisition.